'Moral Person' or 'Ethical Leader'? A Longitudinal Quantitative Analysis of Councilors' Integrity Requirements for Dutch Mayors (2008–2019). (4th May 2022) - Karsten, Niels; Jacobs, Simon P.J.M.
Abstract: Although the scholarly attention for the ethical leadership function in the public sector is increasing, empirical research into the importance of moral norms and values in governance and into what is expected of ethical leaders remains rare. The Dutch mayoralty provides an insightful case in point since a formal ethical leadership role has been attributed to the mayor and because job advertisements for the office are available, which, uniquely, enable tracing the use of the integrity concept. This article provides a quantitative longitudinal analysis of the integrity requirements placed on Dutch mayors in 349 vacancy text. The findings indicate that moral person expectations in particular feature prominently. But, contrary to expectations, the attention paid to integrity requirements for candidate mayors, both as moral persons and as ethical leaders, is found to decrease between 2008 and 2019. This finding may indicate that integrity has increasingly become a taken-for-granted value. In addition, a significant increase is observed in the focus on the role of the mayor in promoting integrity through proactive rather than reactive intervention. Although sanctioning violations remains at its core, the ethical leadership function, thus, seems to be moving towards the taking of preemptive measures.